PERANCANGAN ANIMASI 3D TAMAN WISATA BINJAI PARK DESA JIRAK KABUPATEN SAMBAS - Maya Marselia; Noferianto Sitompul; Fathushahib Fathushahib; M Reza (Indonesian Journal of Business Intelligence (IJUBI), 2022)
3D (three-dimensional) animation is now familiar to most people. The use of 3-dimensional animation is now also increasingly common in filmmaking, advertising, and even as a medium of designing objects and buildings. The purpose of this research was to design and create a 3-dimensional garden animation video that can be used as visualizing objects that appear more real and close to their original form, in the design and creation of this animation researchers use the MDLC (Multimedia Deveploment Life Cycle) method, namely concept, design, material collecting, assembly, testing, and distribution. After that, the process of modeling objects with modeling techniques used, namely primitive modeling and Polygonal Modeling then entered the environment, texture, animating camera operation to the rendering stage using the Blender application, then into pieces of 3-dimensional animated video. After the process is complete, the process of combining videos that have been made in the Blender application and the addition of text and audio using Adobe Premiere Pro cc software. The last stage is the final rendering process that produces a 3-dimensional animation video of the park as a whole in the .mp4 file format with a video duration of 4 minutes